Food Crime - organisierte und organisationale Kriminalität in der Lebensmittelproduktion - Pohlmann, Markus (Waren - Wissen - Raum, 2020)
What is often concealed in the discounter market or at the fruit and vegetable stall is the subject of this article: the dark side of food production and trade. The focus is on the collective forms of illegality that have become established in the production and trade of our food. They are, on the one hand often based on the organized crime of drug cartels, criminal gangs or the mafia. On the other hand, otherwise legally operating companies resort to illegal means from time to time. This collective behavior will be understood as corporate crime. The article examines these two collective forms of crime in more detail and shows their importance using the example of avocados and tomatoes, as well as honey, sausage or fish. The article focuses on identifying the patterns of rule deviations in the field of food crime and on naming key explanatory factors. In particular, the collective rules behind the offenses are elaborated, thus attempting both to contribute to the explanation and indirectly to the fight against food crime.
Keywords: Aufsatz im Buch